THE EFFECT OF SHARIA SUPERVISORY COUNCIL AND SHARIA AUDIT ON SHARIA COMPLIANCE IN SHARIA FINANCIAL INSTITUTIONS IN PEKALONGAN DISTRICT - Sudarmadji, Sudarmadji; Imtikhanah, Sobrotul; Hudaya, Fadli (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aims to obtain empirical evidence and to analyze the influence of Sharia supervisory boards and Sharia audits on Sharia compliance in Islamic financial institutions throughout the Pekalongan district. The population in this study is all management of Islamic financial institutions in the Pekalongan district. Sampling was carried out using the Slovin method which produced 53 samples. The data used is primary data obtained from the results of the questionnaire. The analytical tools used in this study are multiple linear regression, instrument testing, classical assumption testing, and hypothesis testing. Based on the results of hypothesis testing, it is known that the Sharia supervisory board has no effect on Sharia compliance. Meanwhile, Sharia audit has a positive effect on Sharia compliance.